2006
DOI: 10.1158/1078-0432.ccr-05-2468
|View full text |Cite
|
Sign up to set email alerts
|

Combination Analysis of Hypermethylated Wnt-Antagonist Family Genes as a Novel Epigenetic Biomarker Panel for Bladder Cancer Detection

Abstract: Purpose: Aberrant promoter hypermethylation of Wnt-antagonist genes contributes to the pathogenesis of several cancers. We hypothesized that combined methylation analysis of Wntantagonist genes could improve their use as a panel of biomarkers for diagnosing and staging of bladder cancers. Experimental Design: Samples (54 total) of bladder tumor and corresponding normal bladder mucosa were analyzed for the methylation and expression levels of six Wnt-antagonist genes (sFRP-1, sFRP-2, sFRP-4, and sFRP-5,Wif-1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
113
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 26 publications
6
113
1
1
Order By: Relevance
“…We propose that the resultant downregulation of the Dkk3 gene is responsible for the activation of the Wnt/ b-catenin signaling pathway that contributes to the tumorigenesis of cervical cancer. Transcriptional inactivation of Dkk3 associated with promoter hypermethylation has been observed in cancer tissues, including acute lymphoblastic leukemia, nonsmall-cell lung cancer, prostate cancer and bladder cancer, 14,[30][31][32] indicating that the Dkk3 gene may be a frequent target for methylation and silencing in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that the resultant downregulation of the Dkk3 gene is responsible for the activation of the Wnt/ b-catenin signaling pathway that contributes to the tumorigenesis of cervical cancer. Transcriptional inactivation of Dkk3 associated with promoter hypermethylation has been observed in cancer tissues, including acute lymphoblastic leukemia, nonsmall-cell lung cancer, prostate cancer and bladder cancer, 14,[30][31][32] indicating that the Dkk3 gene may be a frequent target for methylation and silencing in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…34 SFRP genes are inactivated by promoter methylation in different human cancers and serve as epigenetic tumor biomarkers. [35][36][37][38] We have demonstrated that SFRP1 is a candidate TSG that is silenced in hepatocarcinogenesis through promoter hypermethylation. 39 To confirm and extend these findings with respect to SFRPs, the methylation status of other SFRP members, including SFRP2, SFRP4 and SFRP5, was also examined by MS-PCR in our study.…”
mentioning
confidence: 99%
“…In recent investigations, several antagonists of Wnt pathway have been identified and can be divided into two functional classes, the secreted frizzled-related protein (sFRP) class and the Dickkopf (Dkk) class [11]. As Wnt-antagonist genes, sFRP-1, sFRP-2, sFRP-4, sFRP-5, Wif-1 and Dkk-3 inhibited Wnt signaling by directly binding to Wnt molecules or by binding to the LRP5/LRP6 component of the Wnt receptor complex.…”
mentioning
confidence: 99%
“…Thus, the functional loss of Wnt antagonists can contribute to activation of the Wnt pathway and induced ectopic expression of ß-catenin. Up to now, downregulation of Wnt-antagonist genes have been identified in a variety of malignancies, including bladder [8,11,12], lung [13,14], breast [15], and chronic lymphocytic leukemia [16], and even the gastric carcinoma [17,18]and esophageal carcinoma [19]. Inactivation caused by promoter hypermethylation seems to be one of the mechanisms underlying down-regulation of the Wnt antagonists, which strongly suggests Wnt-antagonist genes function as tumor suppressor genes may play important role in tumorigenesis.…”
mentioning
confidence: 99%